Effect of probiotics and paraprobiotics on patients with sleep disorders and sub-healthy sleep conditions: a meta-analysis of randomized controlled trials - Yu, Bei; Wang, Ke-Yi; Wang, Ning-Rui; Zhang, Lu; Zhang, Jian-Ping (Frontiers in Neurology, 2024)
Background: The microbial-gut-brain axis has received much attention in recent years, and regulating intestinal flora can effectively improve sleep disorders, which hints the potential effects of probiotics on sleep disorders, but lack of research evidence for meta-analysis. Therefore, this study aims to quantitatively evaluate the influence of probiotics on sleep disorders and sub-healthy sleep conditions. Methods: Up to 2023, online databases including Pubmed, Embase, Cochrane library, Web of science have been searched for studies involving adults who consume probiotics or paraprobiotics in controlled trials, during which, changes in subjective and/or objective sleep parameters and contributing factors in sleeping quality are examined. We conduct a meta-analysis of 11 clinical randomized controlled studies. Results: Probiotic supplementation improves sleep states to some extent in adults with sleep disorders and healthy adults with condition-induced sleep disorders (-0.34 [-0.56–-0.13]; I²=42.6%; P = 0.001; Figure 4 A). Meanwhile, subgroup analysis shows that the effect of probiotics on improving sleep disorders is influenced by other factors such as the health states of the subjects, the duration of the intervention, the type of strain, and the test criteria. Conclusions: Probiotics and paraprobiotics have a significant positive effect on the sleep quality of adults with sleep disorders or sub-healthy sleep conditions. However, the therapeutic effects of probiotics on sleep problems need future additional trials.